2009
DOI: 10.1017/s143192760909504x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Advanced High-Energy Density Li-S Batteries by FE-AEM, SEM/EDS X-ray Spectral Imaging and Feature Sizing/Chemical Typing Techniques

Abstract: Environmentally clean technologies for sustainable energy generation and use are continuously demanding a next generation of long-cycle life high-energy density battery systems, which have higher capacity than existing electrochemical Li-ion and Li-ion/polymer batteries. A light-weight rechargeable cell based on the Li/elemental S redox couple has a highest theoretical specific capacity of 1670 mAh/g of active material and a specific energy of 2600 Wh/kg, assuming complete reaction 2Li. This Sion Li-S battery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…It could result in increased utilization of the electrochemically active poly(S- r -DIB) copolymer in the cathode and retention of this active material upon cycling. These findings are consistent with through-plane direct current (DC) conductivity measurements that show a slight increase in electrical conductivity of the cathode as the fraction of DIB content increases, despite the fact that DIB itself is electrically insulating (Oleshko et al, 2015 a , 2015 b ). This indicates that the incorporation of DIB probably could simultaneously improve the electrical percolation of the carbon nanoparticles in the composite electrodes.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…It could result in increased utilization of the electrochemically active poly(S- r -DIB) copolymer in the cathode and retention of this active material upon cycling. These findings are consistent with through-plane direct current (DC) conductivity measurements that show a slight increase in electrical conductivity of the cathode as the fraction of DIB content increases, despite the fact that DIB itself is electrically insulating (Oleshko et al, 2015 a , 2015 b ). This indicates that the incorporation of DIB probably could simultaneously improve the electrical percolation of the carbon nanoparticles in the composite electrodes.…”
Section: Resultssupporting
confidence: 81%
“…The morphological and compositional variations in the distributions of the poly(S- r -DIB) copolymers and conductive carbon nanoparticles in both the poly(S- r -DIB 10% )-based and poly(S- r -DIB 50% )-based composites will be compared, when possible, to the analogous elemental sulfur-based composite cathodes. Recently, we demonstrated that replacing the elemental α -sulfur (S 8 ) with the poly( S-r -DIB) copolymers may result in molecular level homogeneity and high-capacity/long-life cathode structures that more efficiently generate and transfer charge and are robust against the mechanical stresses that arise from the repeated expansions and contractions during charge/discharge cycling (Simmonds et al, 2014; Oleshko et al, 2015 b ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electron microscopy techniques are widely applied for the determination of structure-property relationships in EES materials by obtaining morphological, crystallographic and local chemical information down to the atomic level. [10][11][12][13][14][15][16][17][18][19][20] S/TEM methods permit real-time examination of various types of batteries during galvanostatic (GS) testing of charge-discharge electrochemical reactions. These methods can additionally probe compression effects and the formation and spatial distribution of the solid-electrolyte-interphase (SEI) under varying processing conditions (temperature, pressure) in situ and ex situ.…”
Section: Introductionmentioning
confidence: 99%